Influential Article Review - Russia's Knowledge In Global Supply Chain Analysis - Clayton, Ernesto; Garza, Samantha; Newman, Alice (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: The objective of this paper is to analyze the scope for improving empirical and methodological foundation of global value chain (GVC) research and for making relevant political decisions, primarily through application of foresight methodology based on the latest trend to combine the approaches of global value chain and national innovation system research. The authors choose Russia as an illustrative case of an economy in the changing geopolitical context to review major trends of global value chains’ development, specific features of Russia’s participation in them, and the necessary steps to increase the quality and efficiency of this participation. Special attention was paid to theoretical, methodological, and empirical tools of GVC research and of making relevant political decisions—which presently are far from being adequate: they need to be supplemented with the new ones to improve the forecasting potential and practical and strategic orientation of the GVC approach. To this end, approaches which would make it possible to research interconnection between global processes and trends with regional and national innovation-based development tendencies become of crucial importance. Application of foresight methodology may significantly contribute to researching the GVC phenomenon, being a major logical step towards creating advanced policy tools to mobilize available resources and coordinate stakeholders’ actions to increase Russia’s global competitiveness. The paper presents a number of case studies which describe practical application of various foresight methodology components to analyze Russian participation in various GVCs, by the examples of specific product and service groups (fresh fruit and vegetables, car parts, mobile phones, air transport, electronic payment systems). The authors conclude that both full-scale foresight studies and specific components thereof could be applied for the purposes of GVC analysis, strategic planning, and making political decisions. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.